2015
DOI: 10.15561/18189172.2015.0207
|View full text |Cite
|
Sign up to set email alerts
|

Indexes of hemodynamics in a dosage of physical activity in girls against the background of low systolic blood pressure

Abstract: Annotation. Purpose: to examine the state of hemodynamics, blood oxygenation levels in girls with hypotensive type neurodystonia in a dosed physical load. Material: The study involved 59 women with hypotensive type neurodystonia aged 18-19 years and 14 healthy women the same age. Results: It was found that the girls on the background of low systolic blood pressure observed early hemodynamic response from the very first steps (25-50 W) bicycle stress test in the form of increased heart rate, stroke volume, puls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…In this connection application of informative and effective methods of control over organism's functional state acquires great importance. Such approach is required for adequate regulation of physical loads depending on human individual features [23,35,37,44,47]. It should be noted that determination of adults' and children's reactions to physical load by subjective feelings as well as their physiological parameters becomes very important [8].…”
Section: Introductionmentioning
confidence: 99%
“…In this connection application of informative and effective methods of control over organism's functional state acquires great importance. Such approach is required for adequate regulation of physical loads depending on human individual features [23,35,37,44,47]. It should be noted that determination of adults' and children's reactions to physical load by subjective feelings as well as their physiological parameters becomes very important [8].…”
Section: Introductionmentioning
confidence: 99%
“…In this respect cardio vascular system (CVS) and erythrocyte link of homeostasis are the weakest [1,11]. Vegetative and neuro motor regulation of nervous muscular system (NMS) has a number of general systemic structural functional properties, which naturally reflect in state of Ер [44,46].…”
mentioning
confidence: 99%
“…Typological analysis [2,9,11] showed that 42% of the tested female volleyball players have hypo-kinetic, 31% -eukinetic and 27% -hyper-kinetic type of CHD.…”
Section: Resultsmentioning
confidence: 99%
“…The authors offer the program of Nordic walking (12 weeks, thrice a week) [38]; − Nordic Walking reduces resistance to insulin [40]; − Nordic Walking significantly reduces ferritine concentration in blood that explains the registered reduction of iron in organism [39]. As some specialists point non uniformity of CHD types is conditioned by body constitution and is a physiological norm of health [2,6,9]. Study of EPB changes with PL max , depending on CHD type is still out of scientists' attention.…”
Section: Pedagogics Psychologymentioning
confidence: 99%
See 1 more Smart Citation